A Systematic Review of Head and Neck Cancer Health Disparities: A Call for Innovative Research. (8th February 2022) - Nallani, Rohit; Subramanian, Thamara L.; Ferguson‐Square, Kiatana M.; Smith, Joshua B.; White, Jacob; Chiu, Alexander G.; Francis, Carrie L.; Sykes, Kevin J.
Abstract : Objective: (1) Describe the existing head and neck cancer health disparities literature. (2) Contextualize these studies by using the NIMHD research framework (National Institute on Minority Health and Health Disparities). (3) Explore innovative ideas for further study and intervention. Data Sources: Ovid MEDLINE, Embase, Web of Science, and Google Scholar. Review Methods: Databases were systematically searched from inception to April 20, 2020. The PRISMA checklist was followed (Preferred Reporting Items for Systematic Reviews and Meta‐analyses). Two authors reviewed all articles for inclusion. Extracted data included health disparity population and outcomes, study details, and main findings and recommendations. Articles were also classified per the NIMHD research framework. Results: There were 148 articles included for final review. The majority (n = 104) focused on health disparities related to at least race/ethnicity. Greater than two‐thirds of studies (n = 105) identified health disparities specific to health behaviors or clinical outcomes. Interaction between the individual domain of influence and the health system level of influence was most discussed (n = 99, 66.9%). Less than half of studies (n = 61) offered specific recommendations or interventions. Conclusions: There has been extensive study of health disparities for head and neck cancer, largely focusing on individual patient factors or health care access and quality. This review identifies gaps in this research, with large numbers of retrospective database studies and little discussion of potential contributors and explanations for these disparities. We recommend shifting research on disparities upstream toward a focus on community and societal factors, rather than individual, and an evaluation of interventions to promote health equity.